Integration Of Salvador Minuchin's Family System Theory In The Practice Of Divorce Mediation In Religious Courts - rizki amar; Ihram Ahmed Siregar; Isyaq Maulidan (Program Studi Bimbingan Konseling, Fakultas Tarbiyah dan Ilmu Keguruan UIN Bukittinggi, 2025)
Divorce mediation in Religious Courts has thus far been more oriented towards formal legal settlements, even though domestic conflicts also touch on psychological and emotional aspects that require a family counseling approach. This article aims to analyze the potential for integrating Salvador Minuchin's family systems theory into the practice of divorce mediation in Religious Courts. This study uses a qualitative approach with a literature review of mediation regulations, religious court practices, and family systems theory. The analysis is conducted using Minuchin's theory, which emphasizes the balance of structure, subsystem boundaries, and communication patterns within the family. The results of the study show that Minuchin's theory is relevant to strengthening the effectiveness of mediation by shifting the orientation of resolution from legalistic to restorative aspects. Counseling techniques such as active listening, reframing, and empathy building can be integrated into the mediation process to help couples re-understand their roles and relationships. Thus, mediation in the Religious Court is not only a forum for resolving legal disputes but also a platform for reconstructing the family system towards harmony and family integrity.